The Dynamics of Public Green Open Space Availability in Ciputat District, South Tangerang City, 2011–2025 - Ceysara, Andrea Prasasti; Aji, Ananto (Jurnal Penelitian Geografi, 2025)
South Tangerang City, particularly Ciputat District, is experiencing rapid development, which has significant implications for the conversion and reduction of public green open spaces (GOS). In evaluating the availability of GOS, it is essential to consider both the extent of existing green spaces and their alignment with the Regional Spatial Plan. This study aims to analyze changes in the availability of public green open space in Ciputat District from 2011 to 2025 and assess its conformity with the Regional Spatial Plan. A quantitative descriptive approach was employed, with data processed using ArcGIS through overlay and digitization methods. The results indicate that public green open space in Ciputat District increased slightly from 16,268 ha in 2011 to 16,848 ha in 2025. However, this represents only 3.8% of the district’s total area, far below the 20% requirement for public green open space stipulated in the Regional Spatial Plan. These findings highlight a significant shortfall in meeting spatial planning standards, underscoring the urgent need for policy interventions to preserve and expand green open spaces as essential components of sustainable urban development.